Branding Brazil : Transforming Citizenship on Screen - Marsh, Leslie L. (Rutgers University Press, 2021)
Branding Brazil examines a panorama of contemporary cultural productions including film, television, photography, and alternative media to explore the transformation of citizenship in Brazil from 2003 to 2014. A utopian impulse drove the reproduction of Brazilian cultural identity for local and global consumption; cultural production sought social and economic profits, especially greater inclusion of previously marginalized people and places. Marsh asserts that three communicative strategies from branding-promising progress, cultivating buy-in, and resolving contradictions-are the most salient and recurrent practices of nation branding during this historic period. More recent political crises can be understood partly in terms of backlash against marked social and political changes introduced during the branding period. Branding Brazil takes a multi-faceted approach, weaving media studies with politics and cinema studies to reveal that more than a marketing term or project emanating from the state, branding was a cultural phenomenon.